Analisis Proses Preventive Maintenance pada Pump Tank Farm PT. H dengan Metode Fuzzy Failure Mode and Effect Analysis (FMEA) di PT. M - Yosika Novsiano; Ulikaryani; Ghia Pisti Cikarge (Politeknik Negeri Cilacap, 2025)
PT.M with PT. H in the preventive maintenance process of the pump tank farm unit. Before the maintenance process is carried out, an analysis is carried out to determine the priority and scale of potential failures that occur in the pump unit at PT. H. The main purpose of preventive maintenance is to ensure all machinery and equipment are functioning properly and improve their reliability.Â This analysis is carried out as an action to eliminate or reduce the risk of danger, especially for the highest risk priority, before carrying out preventive maintenance. The analysis method used is the fuzzy logic FMEA method through simplification with the Three Triangular Fuzzy Number method. Based on the results of the fuzzy RPN calculation in the table above, there are seven pumps that are prioritized for preventive maintenance actions. The seven pumps are UP-AT-01A, UP-AT-01B, TP-AT-01A, TP-AT-01B, TP-AT-06A, TP-AT-04A and UP AT-03B.